Direct ink writing additive manufacturing of porous alumina-based ceramic cores modified with nanosized MgO. Issue 15 (December 2020) - Tang, Shiyan; Yang, Li; Liu, Xinwang; Li, Guanjin; Jiang, Wenming; Fan, Zitian
Abstract: Alumina-based ceramic cores, widely applied to cast alloy, have been restricted by the increased complexity of castings, the resultant complex equipment and cost. In this research, to address the aforesaid disadvantages, direct ink writing, a green additive manufacturing method, is utilized to directly fabricate a new kind of nanosized MgO strengthened alumina-based ceramic cores. Slurries with various compositions exhibits ideal shear-thinning behaviors, owing to the hydrogen bond formed between polyvinylpyrrolidone and kaolin molecules. We notice that introducing nanosized MgO reduces drying shrinkage of green specimens and greatly promotes liquid-phase sintering, leading to rather more densified samples. Overall, it is anticipated that the current approach is effective in rapidly manufacturing alumina-based ceramics and some other ceramics with high strength, low shrinkage and high quality.